2007
DOI: 10.1063/1.2760159
|View full text |Cite
|
Sign up to set email alerts
|

Inherent linearity in carbon nanotube field-effect transistors

Abstract: The authors consider the suitability of carbon nanotubes for use in analog rf amplifiers, where the linearity of the device is critical. They show that in the limit of large electrostatic gate-channel capacitance, their theory predicts that an Ohmically contacted, ballistic carbon-nanotube-based field-effect transistor is inherently linear. While they have not achieved this limit in their experimental work, they compare the theory to experiment in the limit of small electrostatic gate-channel capacitance and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…SWNTs also have low intrinsic capacitance and, unlike many other envisioned next-generation electronic materials and devices, they are compatible with standard metal oxide semiconductor field-effect transistor (MOSFET) structures [1]. Furthermore, recent work suggests the possibility of highly linear operation as high-frequency amplifiers [48]. These attributes suggest that SWNT arrays might eventually be competitive with silicon or III V semiconductors in next-generation high-frequency devices, with the possibility for operation in the terahertz regime [49,50].…”
Section: High-frequency Properties Of Swnt Tftsmentioning
confidence: 99%
“…SWNTs also have low intrinsic capacitance and, unlike many other envisioned next-generation electronic materials and devices, they are compatible with standard metal oxide semiconductor field-effect transistor (MOSFET) structures [1]. Furthermore, recent work suggests the possibility of highly linear operation as high-frequency amplifiers [48]. These attributes suggest that SWNT arrays might eventually be competitive with silicon or III V semiconductors in next-generation high-frequency devices, with the possibility for operation in the terahertz regime [49,50].…”
Section: High-frequency Properties Of Swnt Tftsmentioning
confidence: 99%
“…Ballistic transport of electrons through semiconducting carbon nanotubes has led to the efforts to develop this transistor, one of the key building blocks of any electronic technology and application. The one-dimensional tube structure (i) allows quantum-capacitance limited operation resulting in low input and feedback capacitance, (ii) significantly reduces the scattering probabilities thus promising good high-frequency performance with low noise figures [3], and (iii) causes the drain current to be linearly dependent on the applied gate voltage promising uniquely linear devices [4]. Recently, devices have been reported with estimated intrinsic transit frequency f T in the range of 80 GHz.…”
mentioning
confidence: 98%
“…Analog devices share many of the same challenges associated with their digital counterparts, but they can be implemented at comparatively lower levels of integration density and in layouts that can better exploit the exceptional electronic and thermal properties of the SWNTs. Furthermore, analog devices require linearity, and it has been demonstrated that SWNTs have the potential to provide linearity well beyond what is possible with silicon or III-V semiconductors (22). Recent reports show some measurements of intrinsic high speed operation in transistors that use individual tubes or unaligned collections of tubes, and in a very recent case the use of a single tube device as a mixer in a radio (23), but without the sorts of layouts or performance that would be needed for realistic applications (20,(23)(24)(25).…”
mentioning
confidence: 99%